Climate change and deforestation increase the vulnerability of Amazonian forests to post‐fire grass invasion. Issue 12 (12th September 2021) - De Faria, Bruno L.; Staal, Arie; Silva, Carlos A.; Martin, Philip A.; Panday, Prajjwal K.; Dantas, Vinicius L.
Abstract: Aim: We aimed to evaluate the vulnerability of the Amazon forest to post‐fire grass invasion under present and future climate scenarios. Location: Amazon Basin. Time period: 1981–2017 and 2070–2099. Major taxa studied: Plants. Methods: We combined a fire–ecosystem model with remote sensing data and empirically‐derived equations to evaluate the effects of a high‐intensity fire (i.e., during an extreme drought) and logging in forest edges on tree canopy, and exotic grass cover under present and unmitigated climate change scenarios. We also contrasted simulated vegetation recovery time (as a function of climate variability) and current fire return intervals to identify areas in which fire–grass feedbacks could lock the system in a grass‐dominated state. Results: Under current climatic conditions, 14% of the Amazon was found to be vulnerable to post‐fire grass invasion, with the south‐eastern Amazon at the highest risk of invasion. We found that under unmitigated climate change, by the end of the century, 21% of the Amazon would be vulnerable to post‐fire grass invasion. In 3% of the Amazon, fire return intervals are already shorter than the time required for grass exclusion by canopy recovery, implying a high risk of irreversible shifts to a fire‐maintained degraded forest grassy state. The south‐eastern region of the Amazon is currently at highest risk of irreversible degradation. Main conclusions: Although resilience is evident in areas with low fire activity, increased fire frequency and intensity could push large Amazon forest areas towards a tipping point, causing transitions to states with low tree and high grass cover.